Analisis Efektivitas Pada Sistem Akuntansi Penggajian Di PT “SKU" - Muhammad Naufal Qais; Ayu Chairina Laksmi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study intends to find out how the payroll system at PT "S". The location of this research was carried out at PT "S" Samarinda. The method used by researchers is qualitative and the technique used is by interviewing PT "S" employees. The results showed that the cause of the delay in payroll was due to the director's financial problems which could not be explained due to company privacy. Therefore this researcher is interested in knowing the results of the reconciliation between the owner and PT "S". But there are still a few weaknesses, namely the financial section still has payroll calculation errors.